Command filtered back-stepping control of a flexible air-breathing hypersonic flight vehicle. (July 2014) - Ji, Yuehui; Zong, Qun; Zhou, Hailiang
Abstract: A theoretical framework of nonlinear flight control is exploited and applied to nonlinear longitudinal dynamics of a generic air-breathing hypersonic flight vehicle. A combination of novelty command filtered back-stepping technology and dynamic inversion methodology is adopted for designing a dynamic state-feedback controller that provides stable tracking of the altitude and velocity reference commands. The novel command filtered back-stepping altitude control obviates the need to compute analytic derivatives in the traditional back-stepping design, providing a simple and effective way for controlling non-linear hypersonic flight vehicle. An input-to-state stability -modular approach is presented by combining command filtered back-stepping method with sliding-mode-based integral filters, input-to-state stability analysis, and small-gain theorem . The stability analysis of the closed-loop system including the flexible dynamic, and the convergence of the system outputs are derived. The proposed control scheme is verified in simulations in a climbing maneuver case of separate velocity and altitude reference commands.